(untitled) (Modern Problems of Metallurgy, 2020)
Pipe-rolling units with an automatic mill are a aggregate production complex that produces hot-rolled pipes of various sizes. The technological process of seamless pipes production, has many stages: flashing the billet into a sleeve, longitudinal rolling in gauge, running in a oblique rolling mill, calibrating and reducing the diameter. Each stage significantly affects the accuracy of the geometric dimensions of the pipes. One of the main parameters characterizing the accuracy of the pipes is their transverse difference namely the size and the nature of the distribution of the pipe wall thickness in the cross section. A significant reserve for saving metal is increasing the accuracy of seamless pipes to avoid different pipe wall thickness. Different pipe wall thickness makes it difficult to get quality pipe screw-thread. The conditions of metal deformation at an injection molding machine with an automatic machine do not exclude the presence of fluctuation of the pipe wall thickness. The best characteristic of the accuracy of finished pipes will be the knowledge of quantitative indicators of the transverse difference of their end sections. The purpose of this work is to determine the variation in wall thickness of hot-rolled casing by means of mathematical statistics methods. The use of statistical data processing methods makes it possible to predict the seamless pipe difference indicator. A statistical analysis of the wall thickness indicator of the end sections showed a high ratio of wall thickness symmetry. An effective way to minimize the symmetric difference component is to optimize the deformation modes along the pipe wall. In this case, a graphical analysis of the distribution of wall thickness showed that the actual difference varies in stochastic dependence. To clarify the general form of the random periodic component of such a dependence, it is advisable to apply methods of harmonic analysis, which will allow us to develop a mathematical model for determining the accuracy of pipes.